2017
DOI: 10.1038/srep39872
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, cardiac disorders and asthma as risk factors for severe organ involvement among adult dengue patients: A matched case-control study

Abstract: Progression to severe organ involvement due to dengue infection has been associated with severe dengue disease, intensive care treatment, and mortality. However, there is a lack of understanding of the impact of pre-existing comorbidities and other risk factors of severe organ involvement among dengue adults. The aim of this retrospective case-control study is to characterize and identify risk factors that predispose dengue adults at risk of progression with severe organ involvement. This study involved 174 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 63 publications
(86 reference statements)
5
53
1
Order By: Relevance
“…Under this perspective, it could be suggested that the use of therapeutically doses of MET in healthy patient could increase AMPK activity, inhibiting the HMGCR function generating a beneficial effects during DENV infection. This suggesting can not be extrapolated to type 2 diabetes patients treated with MET because present evidence indicates that diabetes per se , adversely influence the clinical presentation of any infection because patients have dysfunction in several organs and systems [91] and impairment in host defenses mechanisms [92]. Specifically, type 2 diabetes patients have endothelial dysfunction, which can condition more severe forms of dengue infection[93].…”
Section: Discussionmentioning
confidence: 99%
“…Under this perspective, it could be suggested that the use of therapeutically doses of MET in healthy patient could increase AMPK activity, inhibiting the HMGCR function generating a beneficial effects during DENV infection. This suggesting can not be extrapolated to type 2 diabetes patients treated with MET because present evidence indicates that diabetes per se , adversely influence the clinical presentation of any infection because patients have dysfunction in several organs and systems [91] and impairment in host defenses mechanisms [92]. Specifically, type 2 diabetes patients have endothelial dysfunction, which can condition more severe forms of dengue infection[93].…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the finding in the study by Pang et al which reported that the median length of hospitalization was five days (IQR: 4-7 days) longer in patients with comorbidities than dengue patients without comorbidities. 12 To our knowledge this is the first study to find evidence of increased levels of hyperglycaemia in patients with comorbidities compared to those without any comorbidities. In the study done by Aggarwal et al, diabetes (OR: 2.12; 95% CI:1.34-4.65) (<0.0001) was associated with severe Dengue.…”
Section: Discussionmentioning
confidence: 82%
“…Many travelers are older adults, and older travelers may have more comorbidities [79,80]. Diabetes has been identified as a risk factor for dengue, and so have other comorbidities such as hypertension, cardiovascular disease, and asthma [81,82]. Travelers with sickle cell disease are thought to be at increased risk of severe dengue [83].…”
Section: Host Factors Relevant For Travelersmentioning
confidence: 99%